Training on the SAVI model (Somatic, Auditory, Visual, Intellectual) for Muhammadiyah Madrasah Ibtidaiyah teachers in Magelang Regency - Ari Suryawan; Ahwy Oktradiksa; Purwono Hendradi (Community Empowerment, 2023)
Creating learning media is an ongoing challenge faced by teachers in the classroom instructional process. Science subjects require effective learning media to achieve learning competencies. Teachers still struggle with creating affordable and effective learning media. This empowerment program aims to provide training to Madrasah Ibtidaiyah (elementary school) teachers in Magelang Regency using the SAVI Model to enhance teachers' creativity in teaching. This activity is conducted in three stages: strengthening content, focus group discussion, and media creation. The results achieved in this activity are that teachers can accurately analyze the need for media, analyze media designs, and produce media outputs correctly, which can be used according to needs.